2017
DOI: 10.1186/s12864-017-4373-3
|View full text |Cite|
|
Sign up to set email alerts
|

Multiple functions of CREB-binding protein during postembryonic development: identification of target genes

Abstract: BackgroundJuvenile hormones (JH) and ecdysteroids control postembryonic development in insects. They serve as valuable targets for pest management. Hence, understanding the molecular mechanisms of their action is of crucial importance. CREB-binding protein (CBP) is a universal transcriptional co-regulator. It controls the expression of several genes including those from hormone signaling pathways through co-activation of many transcription factors. However, the role of CBP during postembryonic development in i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
41
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 90 publications
2
41
0
Order By: Relevance
“…Following the publication of this article [ 1 ], the authors found that some of the primers listed in Table 1 are not correct. This mistake occurred during assembly of the primer table and the authors apologize for this error.…”
Section: Correctionmentioning
confidence: 99%
“…Following the publication of this article [ 1 ], the authors found that some of the primers listed in Table 1 are not correct. This mistake occurred during assembly of the primer table and the authors apologize for this error.…”
Section: Correctionmentioning
confidence: 99%
“…Gene Ontology (GO) was started by the GO Consortium in 1998 to focus on studies of the genome of three model organisms: Drosophila Melanogaster (fruit fly), Mus musculus (mouse) and Saccharomyces cerevisiae (brewer’s or baker’s yeast) ( 1–9 ). As a result of its unified and well-structured vocabulary, GO was quickly adopted across an array of genome projects ( 10 ), transcriptome projects ( 11–14 ), proteome projects ( 15 ) and more. GO consists of three sub-ontologies: biological process, cellular component and molecular function.…”
Section: Introductionmentioning
confidence: 99%
“…With the rapid development of high-throughput sequencing, the use of genome ( 10 ), transcriptome ( 11–14 ) and proteome ( 15 ) big data has become a major factor in downstream annotation and data analyses. In following this trend and answering user feedback, WEGO was updated to version 2.0 in 2018.…”
Section: Introductionmentioning
confidence: 99%
“…In Camponotus floridanus (Florida carpenter ant), CBP regulates foraging and scouting behaviours by catalysing histone acetylation (Simola et al, 2016). In Tribolium castaneum (red flour beetle), CBP regulates the juvenile hormone pathway and affects postembryonic development (Roy et al, 2017).…”
Section: Introductionmentioning
confidence: 99%